PERAN DUKUNGAN KELUARGA DALAM MENINGKATKAN PENGETAUAN DAN SELF CARE ACTIVITY PADA PASIEN DIABETES MELLITUS - Rahmi, Hidayatul; Malini, Hema; Huriani, Emil (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Family support is one of the main aspects that will help Diabetes Mellitus patients to maintain self-care activity. Aspects of family support such as informational, instrumental, appreciation and emotional support are needed in daily care. The purpose of this study was to analyze the role of family support for self-care activity in Type 2 Diabetes Mellitus patients in the Padang City Health Center in 2019. The design of this study was quasi experimental with pre and post test non-equivalentt control group. Sampling by simple random sampling with a total sample of 64 respondents (32 people in each group). Data was collected using The Summary Of Diabetes Self-care Activity (SDSCA). The results of the study using the Paired T-Test showed that there was an effect of family support for self-care activity (P = 0,000). Family support can improve the ability of diabetic patients to manage diet and physical activity (exercise). Self care activities related to diet management, physical activity (exercise) and treatment are important aspects for diabetic patients and need support, not only emotional support but also Informational support, awards and instrumentals.